2023
DOI: 10.1371/journal.pone.0280852
|View full text |Cite
|
Sign up to set email alerts
|

Coral Gardens Reef, Belize: An Acropora spp. refugium under threat in a warming world

Abstract: Live coral cover has declined precipitously on Caribbean reefs in recent decades. Acropora cervicornis coral has been particularly decimated, and few Western Atlantic Acropora spp. refugia remain. Coral Gardens, Belize, was identified in 2020 as a long-term refugium for this species. This study assesses changes in live A. cervicornis coral abundance over time at Coral Gardens to monitor the stability of A. cervicornis corals, and to explore potential threats to this important refugium. Live coral cover was doc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(3 citation statements)
references
References 62 publications
(74 reference statements)
0
3
0
Order By: Relevance
“…Our in situ data were higher than the SST data overall except for the summer months July, August, and September when satellite SSTs were lower than in situ measurements. Comparative results from other studies found that SSTs were lower than in situ temperatures [12,13]. The key point is that the satellite data do not match temperature data at the depths where corals are growing.…”
Section: Discussionmentioning
confidence: 70%
See 2 more Smart Citations
“…Our in situ data were higher than the SST data overall except for the summer months July, August, and September when satellite SSTs were lower than in situ measurements. Comparative results from other studies found that SSTs were lower than in situ temperatures [12,13]. The key point is that the satellite data do not match temperature data at the depths where corals are growing.…”
Section: Discussionmentioning
confidence: 70%
“…This study revealed increasing lagoon water temperatures over the course of 10 years. It adds a point of comparison for other sites in Belize (e.g., [3,8,12,13,16,19]) and elsewhere in the Western Caribbean region (e.g., [5]). Temperatures were more variable and higher inside the lagoon than at the nearby reef crest of Carrie Bow Cay).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation